(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. Farnesoid-X-activated receptor (FXR) is considered as an upstream controller which could influence the other key regulatory genes encoding cellular antioxidant defense system. Methods. Thirty-five male Wistar rats (240 ± 20 g) were randomly allocated into five groups: 1) control, 2) received gentamicin (100 mg/kg/d) for three days (GM-3d), 3) seven days (GM-7d), 4) 10 days (GM-10d), and 5) 14 consecutive days (GM-14d). Biochemical measurements of BUN and serum creatinine (SCr), histological assessment of renal samples as well as molecular analysis using real-time qRT-PCR were used to investigate the pattern of changes in different levels. Results. Administration of gentamicin was associated with a significant increase in the BUN and SCr until the 10th day, which then suddenly dropped at the day 14. Meantime, the maximum histological distortion was also seen on the 10th day but in a similar pattern, 14th day was associated with clear improvement. Compared to the control value, the maximum reduction in the mRNA expression of Farnesoid X-activated receptor (FXR), nuclear factor erythroid 2–related factor 2 (Nrf2) and Glutathione cysteine ligase-modulatory subunit (GCLM), occurred at the 3rd and 7th days, respectively. Compared to the control, the mRNA expression of the mentioned genes significantly increased up to day 14. Apart from the 3rd day, the mRNA expression of alpha-glutathione S-transferase (α-GST) and superoxide dismutase (SOD) showed a similar descending and ascending pattern at 7th and 10th days, respectively. Conclusion. The expression of FXR, as an upstream controller gene and its downstream pathways mediated by Nrf2, could play a role in gentamicin-induced nephrotoxicity but the pattern of expression was rather biphasic at the acute phase or the subacute ones. DOI: 10.52547/ijkd.7523